Chemical and nutritional characterization of Chenopodium quinoa Willd (quinoa) grains: A good alternative to nutritious food. (15th May 2019) - Pereira, Eliana; Encina-Zelada, Christian; Barros, Lillian; Gonzales-Barron, Ursula; Cadavez, Vasco; C.F.R. Ferreira, Isabel
Highlights: Chemical composition of black, red and white quinoa grains was explored. Proteins and carbohydrates were main nutrients present. Sucrose and oxalic acid were the major hydrophilic compounds. γ-Tocopherol and linoleic acid were the main lipophilic compounds. The three quinoa varieties presented very similar profiles. Abstract: With the purpose of valuing the species Chenopodium quinoa Willd (quinoa), as well as encouraging the consumption of its grains, this study aimed at providing a detailed evaluation of the nutritional value and chemical composition of several quinoa grains of different colour varieties (black, red and white) from different origins. The results demonstrated an excellent composition, namely in the presence of many compounds of interest, such as organic acids, tocopherols and unsaturated fatty acids, as well as a very favourable nutritional profile, with carbohydrates and proteins being the prominent macronutrients. Regarding the different varieties, statistical analysis showed that there were no significant differences in studied parameters, with the exception of proteins, carbohydrates, oxalic acid, γ-tocopherol and total tocopherols content. Thus, this pseudocereal takes a position of nutritional excellence, compared to others cereals more commonly consumed, thereby representing a promising ingredient for many uses in the food industry.